Frequency Dependence of Transverse Correlation Coefficient in the Yellow Sea - 张燕君 张仁和 李风华 (Chinese physics letters, 2010)
Horizontal correlation is one of the most important characteristic parameters in ocean acoustics. In a shallow water acoustic experiment, we observed that the transverse correlation coemcient is an oscillation function of frequency. A model based on adiabatic normal mode theory in a random inhomogeneous waveguide which is statistically isotropic in a horizontal plane is developed. The theory indicates that the oscillation of the transverse correlation coefficient is mainly due to the normal mode interference.